Psikoanalisis Lacan dalam Novel Selamat Tinggal Karya Tere Liye - Nabila Putri, Ika; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The novel includes several deep psychological aspects that are displayed by the author in detail regarding the problems in the lives of the characters which can be studied using psychoanalysis. The problems of this research are 1) How is the personality development of the characters related to the imagination in the novel Selamat Selamat By Tere Liye?; 2) How is the development of the character's personality related to the symbolic in the novel Goodbye by Tere Liye?; 3) How is the development of the character's personality related to imagery in Tere Liye's Goodbye novel? This research aims to determine the development of the character's personality related to imagination, symbols and reality in the novel Selamat Selamat By Tere Liye. The theory used in this research is the theory of Mana Sikana (2005). The research uses a qualitative approach, descriptive method. The data source for this research is Tere Liye's novel Selamat Selamat, which has 360 pages, hermeneutic data collection techniques, data analysis techniques and content analysis and techniques. validity of triangulation data. The results of the research show that the development of the personality of the imagination in Tere Liye's novel Selamat Selamat, there are 6 data and are found in the characters Sintong Hidup, Mawar Terang Bulan, Ucok, and Bunga. The development of the personality symbol in the novel Goodbye by Tete Liye amounts to 19 data. The characters are Sintong Live, Mawar Terang Bulan, Bunga, and Sultan Pane. Real personality development in the novel Goodbye by Tere Liye is 24 data. The characters are Sintong Tinggal, Inang, Paklik Maman, Jess, Babe Na'im, Mr. Dekan , and Bulik Ninggrum.